Lernanthropid copepods parasitic on marine fishes in Turkish waters, including two new records - Özak Argun Aki̇f; Demi̇rkale İbrahim; Yanar, Alper (Zootaxa, 2016)
A review of Lernanthropidae (Copepoda: Siphonostomatoida) recorded on marine fish species in the Mediterranean and Turkish seas is presented together with the first records of two species of the genus Lernanthropus de Blainville, 1822 that are new to the Turkish coasts. The newly recorded parasites are: Lernanthropus gisleri van Beneden, 1852 from the gill filaments of Umbrina cirrosa (Linnaeus, 1758) and Lernanthropus callionymicola El-Rashidy & Boxshall, 2012 from the gill filaments of the Red Sea immigrant dragonet Callionymus filamentosus Valenciennes, 1837. General morphology, measurements and key diagnostic characters of both species are presented, based on light and scanning electron microscopy. In addition, some contradictions are noted in previous descriptions of L. gisleri and some newly observed structural details of L. callionymicola are also presented.